Understanding Food Insecurity as a Determinant of Health in Pregnancy Within the United States: An Integrative Review - Veronica C. Pasha; Lauren Gerchow; Audrey Lyndon; Maya Clark-Cutaia; Fay Wright (Health Equity)
Background: Food insecurity is a major public health concern in the United States, particularly for pregnant and postpartum individuals. In 2020, ∼13.8 million (10.5%) U.S. households experienced food insecurity. However, the association between food security and pregnancy outcomes in the United States is poorly understood. Purpose: The purpose of this review was to critically appraise the state of the evidence related to food insecurity as a determinant of health within the context of pregnancy in the United States. We also explored the relationship between food insecurity and pregnancy outcomes. Methods: PubMed, CINAHL, Web of Science, and Food and Nutrition Science databases were used. The inclusion criteria were peer-reviewed studies about food (in)security, position articles from professional organizations, and policy articles about pregnancy outcomes and breastfeeding practices. Studies conducted outside of the United States and those without an adequate definition of food (in)security were excluded. Neonatal health outcomes were also excluded. Included articles were critically appraised with the STROBE and Critical Appraisal Skills Program checklists. Results: Nineteen studies met the inclusion criteria. Inconsistencies exist in defining and measuring household food (in)security. Pregnant and postpartum people experienced several adverse physiological and psychological outcomes that impact pregnancy compared with those who do not. Intersections between neighborhood conditions and other economic hardships were identified. Findings regarding the impact of food insecurity on breastfeeding behaviors were mixed, but generally food insecurity was not associated with poor breastfeeding outcomes in adjusted models. Conclusion: Inconsistencies in definitions and measures of food security limit definitive conclusions. There is a need for standardizing definitions and measures of food insecurity, as well as a heightened awareness and policy change to alleviate experiences of food insecurity.